Initial Market Assessment : Country Scoping Note--Ghana - World Bank (Washington, DC, 2015)
Donors could assist in clarifying the role, building the capacity, and potentially helping to secure funding of key disaster risk management organizations in Ghana. Engagement in Ghana to develop private sector property catastrophe risk and agriculture insurance should be seen as a medium term engagement. Banking penetration is low, as is insurance and micro-insurance penetration, even when compared to regional countries. That said, Ghana has seen rapid growth in the micro-insurance market with the number of people covered doubling in the last 3 years. The insurance industry, while competitive, has struggled in recent years with profitability, indicating there could be need for insurance capacity building and improved governance. There may be however opportunities for targeted investments in the northern part of the country more prone to drought, aimed at increasing disaster resilience among vulnerable population using market-mediated solutions. Links could be explored between social welfare programs and market-mediated insurance solutions. For example, the government plans to expand the coverage of the Livelihood Empowerment against Poverty Program (LEAP) by over ten-fold in the next three years. These mechanisms could scale up programs against post flood events or drought events in the north. Donors could support the integration of market-mediated insurance solutions within the social welfare programs. Using local insurance capacity to bear some of the risk and develop the insurance products could also be investigated. Such mechanisms delivered through social welfare programs will create a critical mass of policyholders, which could spur the development of commercial agriculture insurance.